Reconstructing historical exposure to asbestos: the validation of 'educated guesses'. (9th August 2022) - Visonà, S D; Crespi, E; Belluso, E; Capella, S; De Matteis, S; Filippi, F; Lai, M; Loscerbo, R; Meloni, F; Pilia, I; Cocco, P; Colosio, C
Abstract: Background: In both the epidemiological and legal context, the causal attribution of asbestos-related lung diseases requires retrospective exposure assessment (REA). Aims: To assess the correlation between the retrospective assessment of occupational and anthropogenic environmental exposure to asbestos and its content in the lung tissue. Methods: Based on the available exposure information, a team of occupational physicians retrospectively assessed cumulative exposure to asbestos in 24 subjects who died of asbestos-related diseases. The asbestos lung content was analysed using analytical scanning electron microscope (SEM-EDS). The Log10 asbestos fibre count in the autoptic samples was predicted as a function of the Log10 estimated cumulative exposure using univariate regression analysis. Results: The median count of asbestos fibres by grams of dry weight (ff/gdw) in the lung tissue was 81 339 (range 0–2 135 849.06); it was 287 144 (range 0–2 135 849.06) among the occupationally exposed, and 29 671 (range 0–116 891) among the subjects who only had anthropogenic environmental and/or household exposure. Amphiboles, and particularly amosite (52%) and crocidolite (43%), were detected in all the study subjects. Chrysotile was not detected in any of the samples. Overall, the retrospective estimate of lifetime cumulative exposure to asbestos showed a moderate correlation with the total asbestos fibre count in the autoptic lung, with the regression model explaining 38–55% of the total variance. Conclusions: Detailed information on occupational, environmental and household exposure circumstances would be indispensable for experienced industrial hygienists and/or occupational physicians to reliably assess past exposure to amphiboles or mixed types of asbestos. Abstract : In both the medical and legal context, the causal attribution of asbestos-related lung diseases requires retrospective exposure assessment. This study aimed to assess the correlation between the retrospective assessment of asbestos exposure and its actual content in the lung tissue. The results suggested that, although reliable, the retrospective estimates are not perfect and need to be conducted by experts and supported by detailed anamnestic information. Moreover, chrysotile burden, compared to amphiboles, is not a reliable marker of past exposure.